(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis highlights the crucial role of emotional intelligence (EI) in modern military service. It shows that military success depends not only on IQ but largely on EI, which influences stress management, leadership, teamwork, and professional growth. Key EI models by Salovey and Mayer, Goleman, and Bar-On are reviewed, along with international military programs from the USA, Israel, and the UK that improve emotional resilience and decision-making. The study recommends incorporating EI training into Uzbekistan’s military education to enhance overall effectiveness.